FUNGSI GRUP ICR DAKWAH FACEBOOK SEBAGAI SARANA DAKWAH - Arin Kharisma Dewi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This study discusses ICR Dakwah group on Facebook which is useful for spreading Islamic da'wah. Judging from the phenomenon, the development of the times, the influence of social media is very strong for the community. several ways from each era are carried out so that da'wah continues to develop and continues to run as it should. therefore, the author is very interested in analyzing it. The method used is descriptive qualitative method which aims to collect detailed actual information that describes the existing problems. The results of this study have illustrated that a social media forum continues to run well in spreading Islamic da'wah. Social media is very helpful in spreading da'wah today, in which many people prefer social media as a medium of communication and provide news quickly. This is a forum for expressing or communicating with each other in adding knowledge about da'wah according to the times. Penelitian ini membahas grup ICR Dakwah yang ada di facebook yang mana berguna sebagai penyebaran dakwah islam. Dilihat dari fenomenanya, semakin berkembangnya zaman, pengaruh sosial media sangat kuat untuk para masyarakat. Beberapa cara dari setiap zaman dilakukan agar dakwah terus berkembang dan terus berjalan sebagimana mestinya. Metode yang digunakan adalah metode deskriptif kualitatif yang bertujuan untuk mengumpulkan informasi aktual secara rinci yang menggambarkan persoalan yang ada. hasil penelitian ini telah menggambarkan bahwa suatu forum sosial media terus berjalan dengan baik dalam penyebaran dakwah islam. Media sosial sangat membantu dalam penyebaran dakwah masa kini, yang mana banyak masyarakat lebih memilih sosial media sebagai media komunikasi dan memberikan kabar secara cepat. Hal ini merupakan salah satu wadah mengekspresikan atau saling berkomunikasi dalam menambah ilmu tentang dakwah sesuai perkembangan zaman.